Enhancing the mind: a neuroethical perspective on diverse brain enhancement techniques - Vassallo, Marta; Picozzi, Mario (Medicina Historica, 2024)
Advances in medical science have expanded our ability to manipulate health, extending beyond treating diseases to enhancing cognitive and emotional functions. This practice, known as cosmetic neurology, involves using neurologic interventions and psychotropic drugs to improve brain performance, resilience to stress, and overall mental well-being, even in healthy individuals. While these interventions raise critical ethical concerns—such as issues of authenticity, beneficence, non-maleficence, and justice—emerging evidence suggests promising alternatives. Non-invasive brain enhancement techniques and experimental biohacking practices, including lifestyle adjustments and technological interventions, offer innovative pathways for cognitive enhancement. However, ethical investigations into these alternatives remain limited. This paper provides a comprehensive neuroethical analysis of invasive and non-invasive enhancement methods, emphasizing the relative advantages of non-drug-based approaches. It argues that non-invasive techniques present a less ethically fraught and more sustainable alternative to psychotropic drugs, positioning them as viable solutions for advancing the field of brain enhancement.